2014
DOI: 10.1159/000362862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BMI on Cardiovascular Events, Renal Function, and Coronary Artery Calcification

Abstract: Background/Aims: High BMI increases the risk of cardiovascular events (CVEs) in the general population. Conflicting results have been reported on the role of BMI on CVEs and on decline of renal function in patients with chronic kidney disease not on dialysis (CKD). This study evaluates the impact of BMI on CVEs, dialysis initiation, and coronary artery calcification (CAC) in CKD patients. Methods: CKD patients were divided in normal-BMI and high-BMI patients. CVEs, initiation of dialysis, and extent and progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
0
24
0
2
Order By: Relevance
“…Two recent meta-analyses showed that obesity and not only hypertension, but also pre-hypertension, were significant predictors of new onset CKD (Garofalo et al, 2016(Garofalo et al, , 2017. Further analyses showed that high BMI increases also the risk for dialysis initiation but not for CV events (Russo et al, 2014). These important findings confirm that epidemiologic analyses may provide different results, given the different populations examined.…”
Section: Introductionmentioning
confidence: 73%
“…Two recent meta-analyses showed that obesity and not only hypertension, but also pre-hypertension, were significant predictors of new onset CKD (Garofalo et al, 2016(Garofalo et al, , 2017. Further analyses showed that high BMI increases also the risk for dialysis initiation but not for CV events (Russo et al, 2014). These important findings confirm that epidemiologic analyses may provide different results, given the different populations examined.…”
Section: Introductionmentioning
confidence: 73%
“…Such a measure may improve physicians' abilities to identify patients with poor prognoses [109]. One approach involves the discovery of novel biomarkers that may add proper prognostic information on top of already known risk factors [46,107,[110][111][112][113]. Investigators from the Steno Diabetes Center, a prospective cohort that contributed to the comprehension of prognosis of diabetic patients with or without CKD, showed that MMP-1 and MMP-2 are associated with an increased risk of CV events and CV mortality, regardless of age, gender, eGFR, and albuminuria [114].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators found a graded relationship between severity of CKD and CAC score independent of conventional risk factors for atherosclerosis. 12 , 13 Further, diabetic patients with coexistent CKD had a higher prevalence, greater extent, and more rapid progression of CAC. 14 …”
Section: Introductionmentioning
confidence: 95%